(untitled) (Nepal Medical College Journal, 2022)
Oral cancer is one of the most common health dilemmas in several countries of the world. General dental practitioners and medical practitioners play a major role in the recognition of oral mucosal changes that may lead to malignancy. Knowledge, attitude, opinion, skill, and practice of oral cancer among dental and medical students play a pivotal role in cancer prevention, early detection, and management. A comparative study was conducted using pre-structured close ended questionnaires which was aimed to compare the level of adequacy of knowledge, attitude, and diagnostic ability about oral cancer among undergraduate dental and medical students at Nepal Medical College. Out of a total of 210 participants, 54 (35.1%) dental and 100 (64.9%) medical students responded. The result revealed more than 90% of the participants had adequacy in knowledge and attitude and would refer the cases to the specialists. Only 24.1% dental and 65.0% medical students had performed biopsy and cytology. Statistically significant association between adequacy of diagnostic ability and type of study field (p-value <0.001) was found in the study. The overall knowledge and attitude score were found adequate for both medical and dental students, while the diagnostic ability score were inadequate for both the groups. Therefore, this study suggests a need for revision in the curriculum with individual opportunity to interact with oral cancer patients and mandatory continuing education program especially on diagnosis of oral cancer for undergraduate dental and medical students.